PENGARUH PENGGUNAAN MODAL KERJA TERHADAP PROFITABILITAS PADA PT. HANJAYA MANDALA SAMPOERNA Tbk. YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 – 2019 - Sardiansyah, Sardiansyah (OBOR: Oikonomia Borneo, 2020)
This study aims to analyze the effect of using working capital on profitability. The method used in this research is descriptive quantitative and uses an analytical tool, namely financial ratios as a tool to determine the effect of using working capital on profitability at PT. Hanjaya Mandala Sampoerna Tbk. From the results of the analysis, it is known that the use of working capital, namely cash turnover in 2015 to 2019 has decreased but mostly is above industry standards, receivables turnover in 2015 to 2019 fluctuated but was above industry standards and inventory turnover Inventory turnover from 2015 until 2019 has increased but is below industry standards. thus making the use of working capital can affect the profitability of PT. Hanjaya Mandala Sampoerna Tbk